Untangling the roles of RNA helicases in antiviral innate immunity. - Morgane Baldaccini; Sébastien Pfeffer (PLoS Pathogens, 2021)
One of the first layers of protection that metazoans put in place to defend themselves against viruses rely on the use of proteins containing DExD/H-box helicase domains. These members of the duplex RNA-activated ATPase (DRA) family act as sensors of double-stranded RNA (dsRNA) molecules, a universal marker of viral infections. DRAs can be classified into 2 subgroups based on their mode of action: They can either act directly on the dsRNA, or they can trigger a signaling cascade. In the first group, the type III ribonuclease Dicer plays a key role to activate the antiviral RNA interference (RNAi) pathway by cleaving the viral dsRNA into small interfering RNAs (siRNAs). This represents the main innate antiviral immune mechanism in arthropods and nematodes. Even though Dicer is present and functional in mammals, the second group of DRAs, containing the RIG-I-like RNA helicases, appears to have functionally replaced RNAi and activate type I interferon (IFN) response upon dsRNA sensing. However, recent findings tend to blur the frontier between these 2 mechanisms, thereby highlighting the crucial and diverse roles played by RNA helicases in antiviral innate immunity. Here, we will review our current knowledge of the importance of these key proteins in viral infection, with a special focus on the interplay between the 2 main types of response that are activated by dsRNA.